Analisis Program Asuransi Nelayan di Desa Tanjung Pecinan Kecamatan Mangaran Kabupaten Situbondo - Usrotul Hasanah; Poppy Putri Viola Asthauresia (ACTON, 2019)
The Fishermen’s Insurance Program was an innovation of The Marine and Fisheries Department in collaboration with the Situbondo Regency government in order to improve welfare and provide guarantees to fishermen in carrying out their daily work in order to achieve the vision, mission and goals of the Situbondo Regency government. The statement of the problem in this study was how the analysis of the fishermen's insurance program in the Village of Tanjung Pecinan, Mangaran District, Situbondo Regency. The research method was a qualitative research design which used oral data for requiring informants used interactive analysis methods. Based on the data described that the ease of registration has been going well even though there were some fishermen who had not registered themselves, the access to insurance companies was easily. The marine and fisheries department provided an understanding of and the importance of insurance, The socialization to fishermen held 1 – 2 times, the insurance premium payment in the first year was free, because it was government-borne, but in the second year the government had not borne it, the fisherman must pay it. The ownership of fisherman card was one of the requirements that when registering for insurance, at least 65 years old, the fisherman ages average was 25-55 years old, the fisherman who his age more than 55 years old was usually no longer became fisherman because of the physical factors, and they would be replaced by their children or relatives. Most of the fishermen in Tanjung Pecinan were not registered and never received an insurance program from the ministry. They were not using prohibited fishing gear by the government